Environmental and social equity in network design of sustainable closed-loop supply chains - Battaïa, O.; Guillaume, R.; Krug, Z.; Oloruntoba, Richard (2023)
While the whole society is meant to benefit from sustainable development; environmental and social fairness considerations are often overlooked in the design of supply chain networks. The literature acknowledges that a reductionist interpretation of sustainability is often found in existing mathematical formulations due to lack of evaluation of the social dimension. In this paper, we suggest new indicators based on Gini index to measure environmental and social inequalities between regions concerned with installation of new product recovery facilities for the reverse part of a closed-loop supply chain. The initial levels of pollution and unemployment rate in each region are impacted by facility location decisions and corresponding industrial activities. We show through numerical experiments that inequalities between the regions can be diminished as a result of the use of deliberate objectives aiming to reduce environmental and social inequity. Managerial insights and future research directions are also discussed.